Growth hormone deficiency and neurocognitive function in adult survivors of childhood acute lymphoblastic leukemia. Issue 10 (28th January 2019) - Krull, Kevin R.; Li, Chenghong; Phillips, Nicholas S.; Cheung, Yin Ting; Brinkman, Tara M.; Wilson, Carmen L.; Armstrong, Gregory T.; Khan, Raja B.; Merchant, Thomas E.; Sabin, Noah D.; Srivastava, DeoKumar; Pui, Ching‐Hon; et al.
Abstract : Background: The impact of growth hormone deficiency (GHD) on neurocognitive function is poorly understood in survivors of childhood acute lymphoblastic leukemia (ALL). This study examined the contribution of GHD to functional outcomes while adjusting for cranial radiation therapy (CRT). Methods: Adult survivors of ALL (N = 571; 49% female; mean age, 37.4 years; age range, 19.4‐62.2 years) completed neurocognitive tests and self‐reported neurocognitive symptoms, emotional distress, and quality of life. GHD was defined as a previous diagnosis of GHD or a plasma insulin‐like growth factor1 level less than −2.0 standard deviations for sex and age at the time of neurocognitive testing. Hypothyroidism, hypogonadism, sex, age at diagnosis, CRT dose, and intrathecal and high‐dose intravenous methotrexate were included as covariates in multivariable linear regression models. Results: Of the 571 survivors, 298 (52%) had GHD, and those with GHD received higher doses of CRT ( P  = .002). Survivors who had GHD, irrespective of prior growth hormone treatment, demonstrated poorer vocabulary (z‐score, −0.84 vs −0.61; P  = .02), processing speed (z‐score, −0.49 vs −0.30; P  = .04), cognitive flexibility (z‐score, −1.37 vs −0.94; P  = .01), and verbal fluency (z‐score, −0.74 vs −0.44; P  = .001), and they self‐reported more neurocognitive problems and poorer quality of life compared with survivors who did not have GHD. Multivariable and mediation models revealed that GHD was associated with small effects on quality of life (general health, P  = .01; vitality, P  = .01; mental health, P  = .01); and CRT dose accounted for the lower neurocognitive outcomes. Conclusions: Adult survivors of childhood ALL who receive CRT are at risk for GHD, although poor neurocognitive outcomes are determined by CRT dose and not by the presence of GHD. Abstract : Adult survivors of childhood acute lymphoblastic leukemia who receive treatment with cranial radiation therapy are at risk for growth hormone deficiency. However, poor neurocognitive outcomes are determined by cranial radiation therapy dose, and not by the presence of growth hormone deficiency.